2020
DOI: 10.3389/fimmu.2019.03152
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucocorticoid Receptor Dimerization Aggravates LPS-Induced Circulatory and Pulmonary Dysfunction

Abstract: Background: Sepsis, that can be modeled by LPS injections, as an acute systemic inflammation syndrome is the most common cause for acute lung injury (ALI). ALI induces acute respiratory failure leading to hypoxemia, which is often associated with multiple organ failure (MOF). During systemic inflammation, the hypothalamus-pituitary-adrenal axis (HPA) is activated and anti-inflammatory acting glucocorticoids (GCs) are released to overcome the inflammation. GCs activate the GC receptor (GR), which mediates its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…GR dimerization is also required for survival against LPS- and CLP-induced shock via downregulation of Il-1 β ( 41 ) and upregulation of SphK1 ( 40 ) in macrophages. GR dim/dim mice present impaired lung function upon LPS challenge under intensive care treatment, possibly through regulation of Osteopontin (Opn) in lung tissue ( 49 ). So, GR dimers have the potential to control acute inflammation because they induce dimer-dependent genes, the product of which has anti-inflammatory functions (e.g., SPHK1, MKP1) or by repressing pro-inflammatory genes (e.g., Stat1, Il-1 β) in a dimer-dependent way.…”
Section: Role Of Endogenous Gcs In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…GR dimerization is also required for survival against LPS- and CLP-induced shock via downregulation of Il-1 β ( 41 ) and upregulation of SphK1 ( 40 ) in macrophages. GR dim/dim mice present impaired lung function upon LPS challenge under intensive care treatment, possibly through regulation of Osteopontin (Opn) in lung tissue ( 49 ). So, GR dimers have the potential to control acute inflammation because they induce dimer-dependent genes, the product of which has anti-inflammatory functions (e.g., SPHK1, MKP1) or by repressing pro-inflammatory genes (e.g., Stat1, Il-1 β) in a dimer-dependent way.…”
Section: Role Of Endogenous Gcs In Sepsismentioning
confidence: 99%
“…However, the synthetic GC dexamethasone is able to restore this hyporeactivity to noradrenaline injection, probably resulting from rapid non-genomic effects according to the authors as these effects are seen as early as 10 min after dexamethasone administration ( 67 ). On the other hand, this response seems to be dimer dependent, as GR dim/dim mice display an aggravated hemodynamic instability after LPS challenge, reflected by a significantly increased need for norepinephrine to reach hemodynamic stability ( 49 ). GCs also enhance vasoconstrictor response to catecholamines in septic patients, and this effect was stronger in patients with adrenal insufficiency ( 68 ).…”
Section: Role Of Endogenous Gcs In Sepsismentioning
confidence: 99%
“…Glucocorticoid receptor (GR) signaling is important for normal heart function and development (18). Moreover, we have recently demonstrated that impaired GR dimerization aggravated hemodynamic instability and organ dysfunction during LPS-induced circulatory shock (19). Results for GR expression in peripheral blood cells in sepsis are ambivalent (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Each group included six mice. The control group and LPS group were intraperitoneally injected with PBS and LPS (Sigma, 10 mg/Kg), respectively ( Qi et al, 2016 ; Zhai and Guo, 2016 ; Liu et al, 2017 ; Proniewski et al, 2019 ; Wepler et al, 2019 ). Twelve mice were euthanized, and the samples of the heart, lung, liver, and kidney were harvested at 6 h after LPS or PBS treatment.…”
Section: Methodsmentioning
confidence: 99%